A reflection on in vitro methodologies for estimating the glycemic index of foods (Research, Society and Development, 2020)
The Glycemic Index (GI) expresses the relative impact of the food's carbohydrate on the plasma glucose concentration, reflecting the fact that foods with a greater increase in the glycemic response after ingestion have a higher GI and vice versa. Knowledge of the GI of foods can guide the choice of the most appropriate foods for the composition of a healthy diet. However, studies to determine the glycemic index of foods are laborious and time consuming, since they are carried out with the participation of human volunteers. The interest in in vitro methods that can estimate this index has been growing. In this sense, the present study aimed to discuss the application of these in vitro methodologies in the estimation of the “glycemic index”, through a brief narrative review and the test of tests chosen to illustrate the reflection on the theme. The two methods tested here were able to respond to the starch sample and observing the quotes about the methodology allows raising questions such as: the use of in vitro methodologies presents itself as something promising, easy and quick to execute, but there is a need the adoption of a single in vitro methodology of choice, to be equated with in vivo, which allows comparison between generated data and the formation of a database of in vitro GI values.